Heat-resistant and wear-resistant aluminum bar and preparation method thereof
By combining the aluminum alloy matrix with a three-dimensional porous composite framework of polyimide-boron nitride, heat-resistant and wear-resistant aluminum rods are prepared by one-way freeze-drying and pressure impregnation, the problems of reduced strength and insufficient wear resistance in high-temperature environments are solved, and the high strength, high hardness and high thermal stability of the material are achieved.
Patent Information
- Application Number
- CN202410988699.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-23
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional aluminum alloys lose strength in an environment above 150°C and lack wear resistance, making it difficult to meet the requirements of strict service environment.
The composite frame was prepared by 1-10-20 wt% of the aluminum alloy matrix, and the composite frame was prepared by one-way freeze-drying method, and the aluminum alloy melt was combined with the composite frame by pressure impregnation method.
The aluminum rod has the advantages of metal, ceramic and resin materials, and has high strength, high hardness, good thermal stability and low wear rate, which is suitable for more stringent service conditions.
Smart Images

Figure BDA0004958252070000121 
Figure BDA0004958252070000122 
Figure BDA0004958252070000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloys, in particular to a heat-resistant and wear-resistant aluminum rod. Background Art
[0002] Aluminum alloy is an important lightweight metal material with the characteristics of low thermal expansion coefficient, high specific strength, high thermal conductivity and high elastic modulus. It is widely used in aerospace, automobile manufacturing, high-speed trains, mechanical equipment and other fields. Common high-strength aluminum alloys such as 2 series aluminum alloy and 7 series aluminum alloy cannot be used in a working environment above 150°C because the precipitation phase that plays a strengthening role grows, loses continuity and causes a rapid decrease in strength. In addition, the wear resistance of aluminum alloy is poor, which also has a great impact on its application. The main factors affecting the heat and wear resistance of aluminum alloys are alloy composition, microstructure, heat treatment process and surface treatment process. In order to improve the heat and wear resistance of aluminum alloys, research is usually conducted from the aspects of component alloying and surface treatment process, such as adding specific alloying elements such as copper, zirconium, manganese, etc. to improve the strength and heat resistance of the alloy, and improving its wear resistance and heat resistance through surface treatment processes such as plating, anodizing, and micro-arc oxidation. With the rapid development of my country's aerospace, rail transportation, and national defense and military industries, traditional aluminum alloys and common strengthening processes have been difficult to meet the requirements of harsh service environments. Compared with traditional aluminum alloys, aluminum-based composites introduce reinforcement phases of different forms and properties into the aluminum alloy matrix, which can combine the superior performance of different materials and show outstanding advantages such as high specific strength, high specific stiffness, high elastic modulus, heat resistance and wear resistance far exceeding traditional aluminum alloys. Therefore, the application range is wider and the research prospects are more far-reaching. Commonly used reinforcement phases of aluminum-based composites include alumina particles, silicon carbide fibers, carbon nanotubes, graphene, etc. Reinforcements of different forms and properties have different reinforcing effects on the matrix. It is expected that better comprehensive performance can be obtained by compounding different reinforcements. Summary of the invention
[0003] Technical problem to be solved: The technical problem to be solved by the present invention is to provide a heat-resistant and wear-resistant aluminum rod.
[0004] Technical solution: A heat-resistant and wear-resistant aluminum rod is composed of 80-90wt% of an aluminum alloy matrix and 10-20wt% of a polyimide-boron nitride three-dimensional porous composite skeleton. Preferably, the method for preparing the heat-resistant and wear-resistant aluminum rod comprises the following steps: S1. Adding boron nitride particles to a polyamic acid aqueous solution and performing ultrasonic dispersion to obtain a uniform solution; S2. The solution prepared in S1 is injected into a freezing mold, and unidirectionally frozen and dried to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated, and subjected to thermal imidization treatment to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. Place the aluminum alloy on the three-dimensional porous composite skeleton prepared in S3, heat and pressurize the aluminum alloy to melt it, and infiltrate it into the interior of the composite skeleton to obtain a heat-resistant and wear-resistant aluminum rod. Preferably, the concentration of the polyamic acid aqueous solution in step S1 is 15-25 mg / mL. Preferably, the particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm. Preferably, the freezing temperature of step S2 is -90 to -30°C, the freezing time is 1 to 4 hours, the drying temperature is -70 to -50°C, and the drying time is 15 to 25 hours. Preferably, the heating temperature in step S3 is 480-520°C. Preferably, the heating temperature of step S4 is 750-850° C. and the pressure is 60-70 MPa. Preferably, the composition of the aluminum alloy matrix is: Si: 6.8-7.5wt%; Cu: 4.1-5.1wt%; Mg: 0.4-1.0wt%; Mn: 0.5-1.2wt%; Zr: 0.3-0.6wt%; Zn: ≤0.25wt%; and the balance is Al. Preferably, the mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:15-25. Beneficial effects: Compared with the prior art, the present invention has the following characteristics: The wear-resistant and heat-resistant aluminum rod of the present invention uses a polyimide-boron nitride three-dimensional porous composite skeleton as a reinforcement, constructs a composite skeleton of a bionic structure by a freeze-drying method, and composites the aluminum alloy melt with the reinforcement by a pressure infiltration method, so that the aluminum rod has the advantages of metal materials, ceramic materials and resin materials, and has excellent comprehensive performance. Natural biomaterials have simple compositions, but they produce efficient strengthening mechanisms through ingenious and complex microstructures, often showing mechanical properties far superior to their component materials, achieving an organic combination of high strength and high toughness of the material, and summarizing their common material design principles, including soft and hard phase composite, microscopic three-dimensional interpenetration, and specific spatial configuration. Ceramic materials have the advantages of low density, high temperature resistance and excellent mechanical properties, and have been widely used in many fields such as biomedicine, armor and aerospace. They are also important reinforcing phases of metal matrix composites, but their inherent brittleness greatly limits the application field and scope of ceramic materials. Resin materials are of various types, light weight, good toughness and thermal stability, and have a wide range of applications, but their mechanical strength is lower than that of metal and ceramic materials. Using the design principles of high-performance biomaterials, resin materials and ceramic materials are composited with soft and hard phases, and a microscopic three-dimensional interpenetrating porous bionic structure is designed as a composite reinforcement of aluminum rods, which can make aluminum rods have the advantages of metal materials, ceramic materials and resin materials, and achieve the combination of high strength and hardness, high toughness and high stability of materials, so that the materials can be used in more stringent service conditions. The preparation of bionic structural metal materials mainly includes two steps: constructing a reinforcement phase skeleton and infiltrating a metal melt. The freeze-drying method has a high tolerance for the reinforcement phase, and this method can be used for various reinforcement phase components, morphologies and structures. Melt infiltration is to melt the metal at a certain temperature to form a metal melt with a certain flowability, and then in the heat preservation process, the metal melt is driven by gravity and capillary force to infiltrate into the pores of the reinforcement phase skeleton. During the cooling process, the metal melt gradually solidifies and finally composites with the reinforcement phase skeleton. The pressure infiltration method is used to infiltrate the metal melt, that is, the melt is infiltrated into the reinforcement phase skeleton by gas pressure, which can maintain good wettability between the skeleton and the melt, and at the same time enhance the fluidity of the metal melt, so that the two can be fully combined, ensuring high material bonding strength and good component uniformity, thereby obtaining excellent comprehensive performance. Compared with the prior art, the present invention has the following advantages and positive effects: The present invention uses a polyimide-boron nitride three-dimensional porous composite skeleton as a reinforcement, so that the aluminum rod has both the high strength and high heat resistance of polyimide and the high hardness and high wear resistance of boron nitride, and has excellent comprehensive mechanical properties. The present invention adopts a unidirectional freezing freeze-drying method to prepare a three-dimensional porous composite skeleton, which is simple and convenient to operate, and can obtain a porous skeleton similar to a bionic structure, thereby improving the comprehensive performance of the aluminum rod. The invention adopts a pressure infiltration method to composite a three-dimensional porous composite skeleton with an aluminum alloy matrix, the bonding strength between the skeleton and the matrix is high, the structure is uniform and the performance is stable. DETAILED DESCRIPTION In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. Specific preferred examples are as follows: Embodiment 1: A heat-resistant and wear-resistant aluminum rod, which is composed of 90wt% aluminum alloy matrix and 10wt% polyimide-boron nitride three-dimensional porous composite skeleton; The preparation method of the heat-resistant and wear-resistant aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -90°C for 1 h, followed by drying for 15 h at a drying temperature of -70°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 750°C, the pressure is 70MPa, and a heat-resistant and wear-resistant aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 6.8wt%; Cu: 5.1wt%; Mg: 0.4wt%; Mn: 0.5wt%; Zr: 0.6wt%; Zn: 0.25wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:15. Embodiment 2: A heat-resistant and wear-resistant aluminum rod, which is composed of 85wt% aluminum alloy matrix and 15wt% polyimide-boron nitride three-dimensional porous composite skeleton; The preparation method of the heat-resistant and wear-resistant aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -90°C for 1 h, followed by drying for 15 h at a drying temperature of -70°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 750°C, the pressure is 70MPa, and a heat-resistant and wear-resistant aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 7.5wt%; Cu: 4.1wt%; Mg: 1.0wt%; Mn: 1.2wt%; Zr: 0.3wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:15. Embodiment 3: A heat-resistant and wear-resistant aluminum rod, which is composed of 80wt% aluminum alloy matrix and 20wt% polyimide-boron nitride three-dimensional porous composite skeleton; The preparation method of the heat-resistant and wear-resistant aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -90°C for 1 h, followed by drying for 15 h at a drying temperature of -70°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 750°C, the pressure is 70MPa, and a heat-resistant and wear-resistant aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 7.3wt%; Cu: 4.7wt%; Mg: 0.8wt%; Mn: 0.9wt%; Zr: 0.4wt%; Zn: 0.2wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:15. Embodiment 4: A heat-resistant and wear-resistant aluminum rod, which is composed of 85wt% aluminum alloy matrix and 15wt% polyimide-boron nitride three-dimensional porous composite skeleton; The preparation method of the heat-resistant and wear-resistant aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -70°C for 2 hours, and then dried for 15 hours at a drying temperature of -70°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 750°C, the pressure is 70MPa, and a heat-resistant and wear-resistant aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 6.9wt%; Cu: 4.3wt%; Mg: 0.7wt%; Mn: 1.0wt%; Zr: 0.5wt%; Zn: 0.2wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:15. Embodiment 5: A heat-resistant and wear-resistant aluminum rod, which is composed of 85wt% aluminum alloy matrix and 15wt% polyimide-boron nitride three-dimensional porous composite skeleton; The preparation method of the heat-resistant and wear-resistant aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -50°C for 3 hours, and then dried for 15 hours at a drying temperature of -70°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 750°C, the pressure is 70MPa, and a heat-resistant and wear-resistant aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 7.2wt%; Cu: 4.8wt%; Mg: 0.5wt%; Mn: 0.5wt%; Zr: 0.4wt%; Zn: 0.15wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:15. Embodiment 6: A heat-resistant and wear-resistant aluminum rod, which is composed of 85wt% aluminum alloy matrix and 15wt% polyimide-boron nitride three-dimensional porous composite skeleton; The preparation method of the heat-resistant and wear-resistant aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -30°C for 4 hours, and then dried for 15 hours at a drying temperature of -70°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 750°C, the pressure is 70MPa, and a heat-resistant and wear-resistant aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 7.0wt%; Cu: 4.4wt%; Mg: 0.9wt%; Mn: 1.1wt%; Zr: 0.3wt%; Zn: 0.1wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:15. Embodiment 7: A heat-resistant and wear-resistant aluminum rod, which is composed of 85wt% aluminum alloy matrix and 15wt% polyimide-boron nitride three-dimensional porous composite skeleton; The preparation method of the heat-resistant and wear-resistant aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -90°C for 1 h, followed by drying for 20 h at a drying temperature of -60°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 750°C, the pressure is 70MPa, and a heat-resistant and wear-resistant aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 7.2wt%; Cu: 4.9wt%; Mg: 0.7wt%; Mn: 1.0wt%; Zr: 0.5wt%; Zn: 0.2wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:15. Embodiment 8: A heat-resistant and wear-resistant aluminum rod, which is composed of 85wt% aluminum alloy matrix and 15wt% polyimide-boron nitride three-dimensional porous composite skeleton; The preparation method of the heat-resistant and wear-resistant aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -90°C for 1 h, followed by drying for 25 h at a drying temperature of -50°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 750°C, the pressure is 70MPa, and a heat-resistant and wear-resistant aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 6.9wt%; Cu: 5.0wt%; Mg: 0.6wt%; Mn: 0.8wt%; Zr: 0.5wt%; Zn: 0.25wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:15. Embodiment 9: A heat-resistant and wear-resistant aluminum rod, which is composed of 85wt% aluminum alloy matrix and 15wt% polyimide-boron nitride three-dimensional porous composite skeleton; The preparation method of the heat-resistant and wear-resistant aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -90°C for 1 h, followed by drying for 15 h at a drying temperature of -70°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 800°C, the pressure is 65MPa, and a heat-resistant and wear-resistant aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 7.2wt%; Cu: 4.6wt%; Mg: 0.9wt%; Mn: 1.0wt%; Zr: 0.3wt%; Zn: 0.25wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:15. Embodiment 10: A heat-resistant and wear-resistant aluminum rod, which is composed of 85wt% aluminum alloy matrix and 15wt% polyimide-boron nitride three-dimensional porous composite skeleton; The preparation method of the heat-resistant and wear-resistant aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -90°C for 1 h, followed by drying for 15 h at a drying temperature of -70°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 850°C, the pressure is 60MPa, and a heat-resistant and wear-resistant aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 6.8wt%; Cu: 5.0wt%; Mg: 0.6wt%; Mn: 1.2wt%; Zr: 0.4wt%; Zn: 0.2wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:15. Embodiment 11: A heat-resistant and wear-resistant aluminum rod, which is composed of 85wt% aluminum alloy matrix and 15wt% polyimide-boron nitride three-dimensional porous composite skeleton; The preparation method of the heat-resistant and wear-resistant aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -90°C for 1 h, followed by drying for 15 h at a drying temperature of -70°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 800°C, the pressure is 65MPa, and a heat-resistant and wear-resistant aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 7.1wt%; Cu: 4.7wt%; Mg: 0.9wt%; Mn: 1.0wt%; Zr: 0.6wt%; Zn: 0.05wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:20. Embodiment 12: A heat-resistant and wear-resistant aluminum rod, which is composed of 85wt% aluminum alloy matrix and 15wt% polyimide-boron nitride three-dimensional porous composite skeleton; The preparation method of the heat-resistant and wear-resistant aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -90°C for 1 h, followed by drying for 15 h at a drying temperature of -70°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 800°C, the pressure is 65MPa, and a heat-resistant and wear-resistant aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 7.3wt%; Cu: 4.6wt%; Mg: 0.8wt%; Mn: 0.8wt%; Zr: 0.4wt%; Zn: 0.1wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:25. To further illustrate the technical effect of the present invention, the present invention also provides a comparative example, which is as follows: Comparative Example 1: A composite aluminum rod is composed of 95wt% of an aluminum alloy matrix and 5wt% of a polyimide-boron nitride three-dimensional porous composite skeleton; the preparation method of the composite aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -90°C for 1 h, followed by drying for 15 h at a drying temperature of -70°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 750°C, the pressure is 70MPa, and a composite aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 7.4wt%; Cu: 5.0wt%; Mg: 0.4wt%; Mn: 0.6wt%; Zr: 0.3wt%; Zn: 0.2wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:15. Comparative Example 2: A composite aluminum rod is composed of 75wt% of an aluminum alloy matrix and 25wt% of a polyimide-boron nitride three-dimensional porous composite skeleton; the preparation method of the composite aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -90°C for 1 h, followed by drying for 15 h at a drying temperature of -70°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 750°C, the pressure is 70MPa, and a composite aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 7.2wt%; Cu: 4.6wt%; Mg: 0.8wt%; Mn: 0.7wt%; Zr: 0.3wt%; Zn: 0.2wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:15. Comparative Example 3: A composite aluminum rod is composed of 85wt% of an aluminum alloy matrix and 15wt% of a polyimide-boron nitride three-dimensional porous composite skeleton; the preparation method of the composite aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -30°C for 4 hours, and then dried for 25 hours at a drying temperature of -30°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 750°C, the pressure is 70MPa, and a composite aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 6.9wt%; Cu: 4.9wt%; Mg: 0.6wt%; Mn: 0.9wt%; Zr: 0.5wt%; Zn: 0.25wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:15. Comparative Example 4: A composite aluminum rod is composed of 85wt% of an aluminum alloy matrix and 15wt% of a polyimide-boron nitride three-dimensional porous composite skeleton; the preparation method of the composite aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -90°C for 1 h, followed by drying for 15 h at a drying temperature of -70°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 700°C, the pressure is 70MPa, and a composite aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 7.3wt%; Cu: 4.3wt%; Mg: 0.5wt%; Mn: 1.1wt%; Zr: 0.3wt%; Zn: 0.15wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:15. Comparative Example 5: A composite aluminum rod is composed of 85wt% of an aluminum alloy matrix and 15wt% of a polyimide-boron nitride three-dimensional porous composite skeleton; the preparation method of the composite aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -90°C for 1 h, followed by drying for 15 h at a drying temperature of -70°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 900°C, the pressure is 60MPa, and a composite aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 6.9wt%; Cu: 4.8wt%; Mg: 0.9wt%; Mn: 0.6wt%; Zr: 0.6wt%; Zn: 0.15wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:15. Comparative Example 6: A composite aluminum rod is composed of 85wt% of an aluminum alloy matrix and 15wt% of a polyimide-boron nitride three-dimensional porous composite skeleton; the preparation method of the composite aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -90°C for 1 h, followed by drying for 15 h at a drying temperature of -70°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 800°C, the pressure is 65MPa, and a composite aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 7.0wt%; Cu: 4.2wt%; Mg: 0.7wt%; Mn: 1.1wt%; Zr: 0.4wt%; Zn: 0.2wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:10. Comparative Example 7: A composite aluminum rod is composed of 85wt% of an aluminum alloy matrix and 15wt% of a polyimide-boron nitride three-dimensional porous composite skeleton; the preparation method of the composite aluminum rod comprises the following steps: S1. The boron nitride particles were added to a polyamic acid aqueous solution having a concentration of 20 mg / mL and ultrasonically dispersed to obtain a uniform solution; S2. The solution prepared in S1 was injected into a freezing mold for unidirectional freezing at a freezing temperature of -90°C for 1 h, followed by drying for 15 h at a drying temperature of -70°C to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated to 500°C for thermal imidization to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. The aluminum alloy is placed on the three-dimensional porous composite skeleton prepared in S3, heated and pressurized to melt the aluminum alloy, and infiltrated into the interior of the composite skeleton, the heating temperature is 800°C, the pressure is 65MPa, and a composite aluminum rod is obtained; The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm; The composition of the aluminum alloy matrix is: Si: 7.5wt%; Cu: 4.4wt%; Mg: 0.7wt%; Mn: 0.9wt%; Zr: 0.6wt%; Zn: 0.05wt%; the balance is Al; The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:30. The tensile strength of each embodiment and comparative example was tested using a universal testing machine, and the tensile strength was cooled to room temperature after being kept at 300°C for 1 hour for tensile testing, and compared with the tensile strength before heat treatment, with the strength residual rate as its heat resistance performance index; using a friction and wear testing machine, each embodiment and comparative example was subjected to unidirectional friction sliding with the same normal load and friction sliding speed, and the weight loss per unit sliding distance was used as its wear resistance performance index; using a microhardness tester to test the hardness of each embodiment and comparative example, the test results are shown in the table. Table 1 Effect of three-dimensional porous composite skeletons with different weight ratios on the properties of aluminum rods Table 2 Effect of different freeze-drying temperatures of three-dimensional porous composite skeleton on the properties of aluminum rods Table 3 Effect of different infiltration temperatures on the properties of aluminum rods Table 4 Effect of different mass ratios of polyimide and boron nitride particles on the properties of aluminum rods In summary, each embodiment of the present invention has high room temperature tensile strength and high temperature tensile strength, as well as high hardness and low wear rate. Compared with the comparative examples, the embodiments have better wear resistance and heat resistance, excellent comprehensive performance, and broad application prospects.
Claims
1. A heat-resistant and wear-resistant aluminum rod, characterized in that: The aluminum rod is composed of 80-90 wt% of an aluminum alloy matrix and 10-20 wt% of a polyimide-boron nitride three-dimensional porous composite skeleton.
2. The method for preparing the heat-resistant and wear-resistant aluminum rod according to claim 1, characterized in that: The following steps are involved: S1. Adding boron nitride particles to a polyamic acid aqueous solution and performing ultrasonic dispersion to obtain a uniform solution; S2. The solution prepared in S1 is injected into a freezing mold, and unidirectionally frozen and dried to obtain a three-dimensional porous composite skeleton precursor; S3. The three-dimensional porous composite skeleton precursor prepared in S2 is placed in a mold and heated, and subjected to thermal imidization treatment to obtain a polyimide-boron nitride three-dimensional porous composite skeleton; S4. Place the aluminum alloy on the three-dimensional porous composite skeleton prepared in S3, heat and pressurize the aluminum alloy to melt it, and infiltrate it into the interior of the composite skeleton to obtain a heat-resistant and wear-resistant aluminum rod.
3. The method for preparing the heat-resistant and wear-resistant aluminum rod according to claim 2, characterized in that: The concentration of the polyamic acid aqueous solution in step S1 is 15-25 mg / mL.
4. The method for preparing the heat-resistant and wear-resistant aluminum rod according to claim 2, characterized in that: The particle size of the boron nitride particles in step S1 is in the range of 20 to 40 μm.
5. The method for preparing the heat-resistant and wear-resistant aluminum rod according to claim 2, characterized in that: The freezing temperature of step S2 is -90 to -30°C, the freezing time is 1 to 4 hours, the drying temperature is -70 to -50°C, and the drying time is 15 to 25 hours.
6. The method for preparing the heat-resistant and wear-resistant aluminum rod according to claim 2, characterized in that: The heating temperature in step S3 is 480-520°C.
7. The method for preparing the heat-resistant and wear-resistant aluminum rod according to claim 2, characterized in that: The heating temperature of step S4 is 750-850° C. and the pressure is 60-70 MPa.
8. The heat-resistant and wear-resistant aluminum rod according to claim 1, characterized in that: The aluminum alloy matrix comprises the following components: Si: 6.8-7.5wt%; Cu: 4.1-5.1wt%; Mg: 0.4-1.0wt%; Mn: 0.5-1.2wt%; Zr: 0.3-0.6wt%; Zn: ≤0.25wt%; and the balance is Al.
9. The heat-resistant and wear-resistant aluminum rod according to claim 1, characterized in that: The mass ratio of polyimide to boron nitride particles in the polyimide-boron nitride three-dimensional porous composite skeleton is 100:15-25.